Perlindungan Hukum terhadap Hak Ulayat Masyarakat Hukum Adat dalam Pengadaan Tanah Untuk Proyek Strategis Nasional : Studi Kasus Pembangunan Ibu Kota Nusantara di Kalimantan Timur - Muhammad Zaufi Gultom; Rosnidar Sembiring; Zulfi Chairi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Indonesia, as a culturally diverse country, recognizes customary law as an essential part of its social order, particularly ulayat rights as communal land rights of indigenous peoples. The development of the Nusantara Capital City in East Kalimantan, covering 256,142 hectares, raises legal issues regarding the protection of ulayat rights affecting at least 21 of all indigenous communities. This study employs normative legal research with statutory, conceptual and case approaches. The findings reveal regulatory inconsistencies and systemic failures in land acquisition. Ideal legal protection requires a holistic approach through the application of Free, Prior and Informed Consent principles and regulatory harmonization based on social justice.